If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X(4X+5)=2X(X-3)
We move all terms to the left:
X(4X+5)-(2X(X-3))=0
We multiply parentheses
4X^2+5X-(2X(X-3))=0
We calculate terms in parentheses: -(2X(X-3)), so:We get rid of parentheses
2X(X-3)
We multiply parentheses
2X^2-6X
Back to the equation:
-(2X^2-6X)
4X^2-2X^2+5X+6X=0
We add all the numbers together, and all the variables
2X^2+11X=0
a = 2; b = 11; c = 0;
Δ = b2-4ac
Δ = 112-4·2·0
Δ = 121
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{121}=11$$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(11)-11}{2*2}=\frac{-22}{4} =-5+1/2 $$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(11)+11}{2*2}=\frac{0}{4} =0 $
| 5x+25=14x-14 | | 3*x+5=50 | | 3xx+5=50 | | 2x÷4=5 | | X(2+x)=27 | | 2x+48-24x=-22 | | 3÷4=x | | 3x–8+4–2x=14 | | 5x=3+5x | | 7x+6+4x=9-2x+7+81 | | -1+4y=-4+25y | | 3y+6=-64-7y | | 10+5x=20+x | | 3x-1=5-4x-1 | | 6+11y=6+y | | 4-x=13+3x-1 | | 13y=-104 | | 2x−13=−7 | | 2*y+7=12 | | (3x-1)(2x+3)=39 | | -16+4x=-24=15x | | x+x(.10)=111 | | 1/4(3x−1)=2x−2/3 | | 2z/7-6=1 | | 4x²-169=0 | | F(x)=5x/x+1 | | 500x^2-300x+44,8=0 | | 500x^2-30000x+44,8=0 | | F(x)=2x2+5x-4 | | 50/100=12/x | | (2+z)/3=5 | | 4x+(3x-29)=29 |